L'assimilation vocalique régressive en bamanankan: de différents cas - Diallo, Mohamed (Lingua Posnaniensis, 2010)
The aim of this article is to furnish more information about the vocalic regressive assimilation, which is the most frequent phonological phenomenon in Bamanankan. Nearby the adjectives, post-positions, adverbs, the plural morpheme and the distributive morpheme is described also the behaviour of some other conjonctions, particles, and particular cases of assimilation which have been not taken into account in the preceding article. For the comments and remarks on some categories of word we will refer to the chapters concerning them. The description will always concern only the case where the two consecutive words present different vowels. The language which is the topic of this contribution is called bámánánkán. The speakers are named bámánán. It is very known under the name bambara. The bamanankan is the most important language among the 13 languages which are recognized officially as national languages of the Republic of Mali. It belongs to the Manding which is a group of Mande Languages which are in their turn an under family of Niger-Congo.